New subgenus Monilistylus subgen. n. and a new species Procloeon (Monilistylus) ornatipennis sp. n. (Ephemeroptera: Baetidae: Procloeon) - Kluge, Nikita J. (Zootaxa, 2020)
The new subgenus Monilistylus subgen. n. is described based on imaginal and larval characters. Its type species is Procloeon (Monilistylus) monilistylus Kluge, Tiunova & Novikova 2014 from the Russian Far East, known as larvae, subimagines, imagines of both sexes and eggs associated by rearing. Male larva, subimago and imago of Procloeon (Monilistylus) ornatipennis sp. n. are described based on reared specimens from Lombok (Indonesia).